Can contract farming improve farmers’ technical efficiency and income? Evidence from beef cattle farmers in China - Liang, Yuan; Bi, Wentai; Zhang, Yuejie (Frontiers in Sustainable Food Systems, 2023)
Introduction:Contract farming is seen as a tool to create new market opportunities that can address market imperfections in many developing countries and thus increase smallholder income. Methods:This study examines the impact of contract farming on farm household income using survey data from 610 rural households in China. The propensity score matching method addresses the sample selection bias of participation in contract farming. Results:Contract farming can significantly increase farmers’ income, and both marketing contracts and production-management contracts can substantially increase farmers’ income levels, with production-management contracts having a greater degree of impact. Additional analysis reveals that breeding years, farm size, and training time can significantly affect how contract farming enhances farmers’ income. Further analysis shows that agricultural production technical efficiency partially mediates the effects of contract farming on farm household income. Discussion:Contract farming can be an effective institutional arrangement for improving the technical efficiency of farm household production and revenue. We also point out that the government needs to encourage and support smallholders to engage in deeper cooperation with companies, and enhance the organization of farmers to promote the sustainable and high-quality development of China’s beef cattle industry.